(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The essay explores the possibilities of a decolonial feminist reading of two collections of short stories by Asja Bakić, titled Mars and Sladostrašće (Lust), with reference to the critical thought developed by Gloria Anzaldúa and María Lugones. The analysis of the positionality of the narrator and the main motifs reveals facets of the features of ‘border thinking’, situated in the specific experiences of marginality and the workings of the hegemonic structures. Decolonial feminism is identified as a suitable analytical framework to engage the contexts of multiple exposures to violent ideologies and patriarchal order. Elements of the rhetoric of modernity, such as development, progress, anthropocentric and technological thinking as presented in the writing of Asja Bakić, are utilized to create the scenery for the violence that is instrumental for the preservation of existing hierarchies. Simultaneously, Bakić also succeeds in avoiding the trap of the essentialized gender representation. Furthermore, frequent references to European literary heritage used by the author are not attempts at cultural appropriation or an expression of an aspiration towards ‘Europeanness’ but offer a means to express or reaffirm literary forms of resistance to the hypocrisy of bourgeois morality and its inherent dehumanization of the ‘other’. Asja Bakić’s stories resist genre classification. This appears to be a deliberate subversion, rather than an incidental outcome of imaginative storytelling by the author. This move is made as an articulation of the Self enmeshed with a reflection of particular social and historical circumstances. Elements of fantasy and mythology are entangled with the memories of socialism and sexual imagery with pornographic hints. The underlying themes of these stories involve power and resistance to power, agency, seizing control, seeking out freedom and taking liberties. Asja Bakić creates literary worlds that – through destabilization, displacement and humor – challenge the imposed ‘universality’ of the male gaze, while at the same time refusing to participate in the fragmentation and dehumanization of her own readership.